First results of the AMYPAD Prognostic and Natural History Study: amyloid‐PET centiloids predicts cognitive functioning in a pre‐dementia population. (20th December 2022) - García, David Vállez; Collij, Lyduine E.; Mastenbroek, Sophie E; Alves, Isadora Lopes; Gispert, Juan Domingo; Ritchie, Craig W.; Boada, Mercè; Marquié, Marta; Grau‐Rivera, Oriol; Fauria, Karine; Scheltens, Philip; Vandenberghe, Rik; et al.
Abstract: Background: The AMYPAD Prognostic and Natural History Study aims to evaluate the value of (semi‐)quantitative amyloid PET imaging for predicting progression within an Alzheimer's disease risk probability spectrum. The project is actively recruiting non‐demented participants from 17 sites across Europe, with a particular interest in those with emerging amyloid pathology. Method: As of 17 th January 2022, a total of 1, 460 participants had been included. Of those, clinical data of 1, 015 were processed, with 688 (68%) having at least a quantified amyloid PET at baseline, with [ 18 F]flutemetamol or [ 18 F]florbetaben. The primary metric used to assess amyloid burden was the Centiloid (CL), measured from the ratio of the GAAIN cortical target and whole cerebellum. Scans were categorized as negative (CL≤12), gray‐zone (12<CL≤50), or positive (CL>50). The distribution of these groups was assessed using a Gaussian mixture model. Independent linear mixed‐effect models were used to explore the predictive value of CL, and its interaction with time, for several cognitive outcomes: mini‐mental state examination (MMSE), memory (immediate recall, IR), attention (digit‐span forward, DSF), language, visuospatial, and executive functions. In addition, years from baseline, parent cohort, age, sex, education, APOE‐ε4, and the Clinical Dementia Rating (CDR) score were used as independent variables. Result: Demographics are shown in Table 1 . At baseline, 88% of the subjects were classified as cognitively unimpaired (CDR=0). A majority of 384 (56%) was categorized as negative (1±7CL), 210 (30%) as grey‐zone (14±11CL), and 94 (14%) as positive (58±31CL) [Figure 1 ]. Baseline CL (‐0.007 [‐0.010; ‐0.004]) and its interaction with time (‐0.002 [‐0.003; ‐0.001]) were predictive of IR. Baseline CL, but not its interaction with time, predicted MMSE (‐0.007, 95%CI [‐0.010; ‐0.003]) and DSF (‐0.003 [‐0.005; ‐0.001]) [Figure 2 ]. No significant relationships were observed for executive, language, or visuospatial function. Conclusion: Higher baseline CL were associated with lower global cognitive function and attention scores. Whereas, higher CL were associated with a steeper memory decline over time. Current results suggest that cerebral amyloid accumulation is predictive of future overall cognitive function, attention, and memory decline. Further analysis is assured, including more participants, longitudinal PET outcomes, and other biomarkers of the disease.